A Descriptive Analysis of State Government Debt‐Related Derivatives Policies. (June 2014) - Singla, Akheil; Luby, Martin J.
ABSTRACT The increasing use of debt‐related derivatives over the last 10 years, combined with the recent global financial crisis' impact on these instruments, greatly affected the finances of many state and local governments in the United States. Some observers believe the negative effects could have been minimized had governments established prudent financial risk management policies governing these products. This research describes and analyzes debt‐related derivatives policies at the state level. It finds that while 30 states used debt‐related derivatives between 2005 and 2010, only 20 states have policies guiding financial derivative practices, with the policies being of varying breadth and depth.